PENGGUNAAN PUPUK ORGANIK MIKROORGANISME LOKAL UNTUK PENERAPAN PRAKTIK PERTANIAN BERKELANJUTAN DI DESA MONTONG BAAN - Amini, Lulu’; Asyiqin, Ulfa Ainun; Ningrum, Melliana Putri Hendri; Rosada, Baiq Amrina; Pebriani, Ni Komang Putri; Oktaviani, Siti Amanda; Aulia, Mina; Ningrat, Ghalih Ramdhan; Pariji, Deni Liwal; Fitri, Naely Nur’aida; Markum (Universitas Mataram, 2025)
The Community Service Program (KKN) in Montong Baan Village aimed to reduce farmers’ dependence on chemical fertilizers by introducing Local Microorganism (MOL) liquid fertilizer. The activities included surveys, socialization, hands-on practice, and monitoring of the fermentation process. MOL was formulated from banana corms, rice-washing water, and palm sugar, then fermented for 14 days. The results showed a brown liquid with a fermented aroma similar to tape, indicating successful fermentation. The community responded positively, with some farmers starting to apply MOL to chili plants that appeared fresher. This program provided economic benefits by reducing fertilizer costs, social benefits through improved skills and environmental awareness, and ecological benefits by decreasing the negative impacts of chemical fertilizers on soil and water. Furthermore, village leaders and the Village-Owned Enterprise (BUMDes) initiated independent MOL production, ensuring program sustainability. Thus, the KKN program contributed to community empowerment and promoted sustainable agriculture based on the green economy